Serological, electrophoretic, and biological properties of Cryptococcus neoformans antigens. - Murphy, J W (1988)
We compared a cryptococcal culture filtrate antigen referred to as CneF with chemically defined cryptococcal antigen fractions isolated by Cherniak and co-workers by using double immunodiffusion gels, polyacrylamide gel electrophoresis, immunoblots, and footpad reactivity of immunized mice. The three previously described components of cryptococcal culture filtrates are a high-molecular-weight glucuronoxylo-mannan (GXM), which is the major constituent, a galactoxylomannan (GaIXM), and a mannoprotein (MP). In this study we demonstrated that CneF contained components which were serologically and electrophoretically similar to the three previously described cryptococcal culture filtrate fractions. The MP fraction elicited significantly stronger delayed-type hypersensitivity responses than did the GXM or GaIXM fraction when used in mice immunized either with the CneF in complete Freund adjuvant or whole heat-killed Cryptococcus neoformans yeast cells. These findings were confirmed when the footpads of immunized mice were challenged with GaIXM and MP preparations from a culture filtrate of a C. neoformans acapsular mutant that does not produce GXM. Thus, we concluded that the MP was the primary component recognized by the anticryptococcal cell-mediated immune response in mice.